2022
DOI: 10.17221/151/2021-swr
|View full text |Cite
|
Sign up to set email alerts
|

Causes clarification of the soil aggregates stability on mulched soil

Abstract: Soil aggregates have great effects on soil properties and soil functions. Mulching (organic inputs) has been known as a factor influencing soil aggregate stability. Our study aimed to reveal the causes of the higher stability of soil aggregates under organic mulches. The primary soil characteristics such as organic carbon (Cox), humus quality (E4/E6), potential wettability index (PWI), and aromaticity index (iAR) were determined. The Cox was measured using rapid dichromate oxidation, and E4/E6 was measured usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…If performed correctly, this method is capable of producing very good results characterizing soil organic matter. Our study's results agree with Thai et al [55] and demonstrate that the E4/E6 method is unfit for the determination of soil organic matter quality, and was therefore not used in further evaluations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…If performed correctly, this method is capable of producing very good results characterizing soil organic matter. Our study's results agree with Thai et al [55] and demonstrate that the E4/E6 method is unfit for the determination of soil organic matter quality, and was therefore not used in further evaluations.…”
Section: Discussionsupporting
confidence: 86%
“…A significant correlation between EEG and PWI (0.735, p < 0.01) is in accordance with this hypothesis. The aromaticity index (IAR) also expresses the stability of soil organic matter [55]. Treatments with organic fertilizers produce significantly higher values.…”
Section: Potential Wettability Indexmentioning
confidence: 99%
“…This indicates that the immediate impact of various mulches on soil pH, which resulted in high differences between the values from different scenarios (Pavlů et al, 2021), diminished. The reason in both cases can be a gradual decomposition of all mulches and leaching of the selected compounds towards groundwater that resulted in different composition of aggregate's cementing agents in time (Thai et al, 2022). The EC values in Table 1 (which were not measured in our previous study) showed that the salinity under organic mulches (particularly under WCH cover) was much larger than that for the control plots (NMU) and the CRS plots.…”
Section: Resultsmentioning
confidence: 69%
“…Wood chips or gravels are preferred in gardening. Different materials then have different effects on soil water and thermic regimes, and consequently also on other soil properties (e.g., Al-Shammary et al, 2020;Hlaváčiková et al 2019;Kader et al, 2017;Kasirajan and Ngouajio, 2012;Kodešová et al, 2014;Pavlů et al, 2021;Qu et al, 2019;Thai et al, 2022;Wang et al, 2021;Yang et al, 2020). For instance, Pavlů et al (2021) studied soil properties in 27 perennial patches covered by eight different mulch materials (bark chips, wood chips, wheat straw, cardboard, paper foil, decomposable matting, nonwoven fabric covered by bark chips, and crushed basalt) and control patches without any mulch during the 4-year period.…”
Section: Introductionmentioning
confidence: 99%
“…It was contrast to the finding of Ohno et al (2014) where the abundance of condensed aromaticity of SOM was much lower in subsoil under coniferous and deciduous forests due to the adsorption of aromatic compounds to the minerals present in the soil profiles. The decrease or increase of the iAR through the soil profile, generally, depends on the association of plant residue compositions, climate conditions, and microorganism present in the soil (Koutika et al 2020;Thai et al 2022). The lower aromaticity in the uppermost soil layer than in the deeper soil profile under both forest tree species, however, was indicated by the less humified and decomposed organic matter due to the chemical and physical interaction mechanisms (Chen et al 2013;Corvasce et al 2006).…”
Section: Soil Organic Carbon Indices Of Soil Wettability Aromaticity ...mentioning
confidence: 99%